Faham Ilmu Dalam Islam: Pengamatan Terhadap Tiga Takrifan Utama Ilmu - Ismail, Mohd Zaidi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2009)
Although past Muslim scholars had offered many definitions and descriptions of knowledge, if each description is used on the right occasion, it may then shed light on some aspects and characteristics of knowledge which are not properly dealt with by the other descriptions. This article focuses on three such descriptions, each functioning to make manifest certain important and principal features and attributes of knowledge. The first description emphasizes that knowledge is an attribute of man that enlightens; the second description summarizes it as a belief or conviction that is true, certain and based on right proofs; while the third description, as reformulated by S. M. N. al-Attas, explains knowledge as the arrival in the soul of the meaning of a thing as well as the arrival of the soul at the meaning of a thing.